Dynamics of Characters Elinor and Marianne in Austen’s Sense and Sensibility - Nur Sapta Riskiawati; Muh Fauzi Razak (PT FORMOSA CENDEKIA GLOBAL, 2022)
In the author’s works, some of their work are mostly inspired by the environment around them. In this research, the writer focuses to search the dynamic character in the novel Sense and Sensibility and comparing the situation from Austen’s experiences and the characters from the novel. The writer uses dynamic structuralism approach to analyze the intrinsic elements of the novel and biography approach to analyze the background of author’s life. Based on the results of this analysis, Jane Austen created the dynamic of the character become so real and live. In this novel, the characters Elinor and Mariane have important role in the novel and have similarity with the writer4. The writer sums up that Sense and Sensibility is one of the famous novels that has good literary values. The reader can learn much about life, moral, love and loyality from this novel.